1973
DOI: 10.2105/ajph.63.12.1029
|View full text |Cite
|
Sign up to set email alerts
|

Fears of genocide among black Americans as related to age, sex, and region.

Abstract: The results of this study indicate that black Amercans, especially young black males, are suspicious that genocide is the aim of family planning programs controlled by whites. Black women are more positively inclined to family planning. There is altogether an ambivalence created by the fear of genocide and a desire to use family planning methods. This dilemma will remain until the life circumstances of black Amencans improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…These findings are generally consistent with previous studies by Darity and Turner (1972and Turner ( , 1973 as well as others who suggest that fears of genocide and negative attitudes toward family planning/ birth control may be an obstacle to creating meaningful family planning strategies for Blacks in an uraban context. Our findings indicate that these feelings exist for Blacks in rural communities as well.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are generally consistent with previous studies by Darity and Turner (1972and Turner ( , 1973 as well as others who suggest that fears of genocide and negative attitudes toward family planning/ birth control may be an obstacle to creating meaningful family planning strategies for Blacks in an uraban context. Our findings indicate that these feelings exist for Blacks in rural communities as well.…”
Section: Discussionsupporting
confidence: 92%
“…He recommended a rehabilitation and guidance program for job placement. Turner and Darity (1973) also documented a marked fear of genocide among northern and southern urban Black populations, and found &dquo;that genocide fears of Black Americans are continuing to create barriers to the effective use of family planning methods&dquo; (p. 1034). In a 1972 study, Darity and Turner examined family planning attitudes, race consciousness and fear of genocide among Afro-Americans and determined that their genocide fears were a response &dquo;to a long history of every possible type of oppression which has been perpetrated against Blacks&dquo; (p. 1459).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Its first empirical link to public health was made in the 1970s when Turner and Darity (1973) conducted research with 1,890 black Americans in three cities to assess their attitudes toward family planning. Over 20 years ago, these authors reported that fear of genocide was the common reaction toward birth control programs.…”
Section: Genocide: From Family Planning To Aidsmentioning
confidence: 99%
“…For instance, in the early 1970s, Turner and Darity (1973) documented African Americans' concerns that family planning was being used against them as a form of genocide; 39% of the African Americans surveyed believed that ''birth control programs are a plot to eliminate blacks.'' A survey in the early 1990s found that 35% of black church members thought that AIDS was a form of genocide, GUINEA PIG KIDS and an additional 35% were unsure (Epstein 1997).…”
Section: Distrust and Rumorsmentioning
confidence: 99%